Selfies : why we love (and hate) them - Tiidenberg, Katrin (Bingley, U.K. : Emerald Publishing Limited, 2018)
This book brings a rich and nuanced analysis of selfie culture. It shows how selfies gain their meanings, illustrates different selfie practices, explores how selfies make us feel and why they have the power to make us feel anything, and unpacks how selfie practices and selfie related norms have changed or might change in the future. As humans, we have a long history of being drawn to images, of communicating visually, and being enchanted with (our own) faces. Every day we share hundreds of millions of photos on Facebook, Instagram and Snapchat. Selfies are continually and passionately talked about. People take vast amounts of selfies, and generate more attention than most other social media content. But selfies are persistently attacked as being unworthy of all of this attention: they lack artistic merit; indicate a pathological fascination with one's self; or attribute to dangerously stupid behaviour. This book explores the social, cultural and technological context surrounding selfies and their subsequent meaning.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Selfies (Photography) -- Social aspects; Social media -- Research; Digital images -- Social aspects; Self-portraits -- Social aspects; Social Science -- Media Studies; Popular culture